Political developments and the Constitution -making of the Republic of South Korea - Hongchumphae, Paphat (Journal of Asia Social Science Studies, 2025)
An article on the political developments and the Constitution -making of the Republic of South Korea aims to point out the basic relationship between constitution-making and various stages of political development. Political development has had an effect on changes in the constitution- making of the country in the six eras of the republic. At the first stage of political development, it was under the influence of civilian dictatorships before developing into a military dictatorship later on. By preparing the Constitution of the Republic of South Korea Influenced and supported by the United States, its three main characteristics are the existence of a written constitution, the confirmation of people’s rights in the Constitution, and having only one constitution as the basis. Administrative leaders use the constitution as a tool to gain power and inherit the power to govern the country. Creating and amending the constitution to provide the law for the succession of power in governing the country by the elite group is important. Before the public sector could participate in governance during the Sixth Republic era, political developments greatly affected the process of drafting and amending the Constitution of the Republic of South Korea. It be seen from the first six amendments to the Constitution that they were intended to ensure the succession of political power to the ruling dictator. The political development changed with people participating in politics and government in the later period. This led to the drafting of a new constitution for the seventh to ninth time. The constitution helped lay the foundation for politics and governance to be more acceptable to South Korean society.